COMPARISON ANALYSIS OF EARTHING RESISTANCE VALUE BETWEEN PLANTED ELECTRODES IN GROUND AND AROUND SEPTIC TANK (Case Study Of Dahlia Housing In Kendari City) - Hardiman, Hardiman; Jie, Samuel; Hay, Sahabuddin (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2019)
The earthing system aims to secure electrical tool equipment as well as human in the vicinity of the disturbance by streaming the disturbance to the earth. Based on PUIL, the feasibility of the land must have a maximum value of 5 ohms (PUIL 2000 ; 68). One element that needs to be considered in the measurement of an earth system to obtain a small resistance value is the condition of the ground in the area where the earthing system will be installed.In this study we compared the value of earth resistance with elecrode planted in ordinary ground and with electrode planted on the ground around the septic tank varying in the depth and number of the electrode.From the results of the analysis it was concluded that the value of earth resistance was strongly influenced by the depth of the electrode planted the distance between the electrode and the ground conditions where the electrode planted.Keywords : earthing resistance, electrode, septic tanks, ordinary soil.